Zomerbeelden. (Goes : Culturele Raad Goes, 1994)
Blokland, Wido ; Claassen, Tom ; Rheinsberg, Raffael ; Bakker, Wim ; Dijkstra, Florette ; van Dokkum, Ronald ; Otte, Ineke ; Overtoom, Marry ; etc.
Zomerbeelden Goes, 18 juni t/m 16 juli 1994
boek